2010
DOI: 10.1016/j.bmc.2010.07.026
|View full text |Cite
|
Sign up to set email alerts
|

New antitumoral agents I: In vitro anticancer activity and in vivo acute toxicity of synthetic 1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadien-3-one and derivatives

Abstract: This paper describes a new method for the preparation of 1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadien-3-one 1 and its derivatives 2-5. This set of synthetic compounds exhibited high antitumoral activities regarding in vitro screening against several human tumor cell lines as lung carcinoma NCI-460, melanoma UACC-62, breast MCF-7, colon HT-29, renal 786-O, ovarian OVCAR-03 and ovarian expressing the resistance phenotype for adriamycin NCI-ADR/RES, prostate PC-3, and leukemia K-562. Compounds were also teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Thus, 22 presents potent proapoptotic and anti-angiogenic assets in vitro and in vivo , suggesting it to be a potential and promising remedy for treatment of ER-negative breast cancer. Other in vivo rodent studies not specifically reviewed here are likewise encouraging that the wide-ranging MAC family of anti-inflammatory and anti-cancer agents may well be able to address the corresponding debilitating conditions in humans sometime in the future [ 8 , 15 , 16 , 17 , 67 , 68 , 90 , 97 , 110 , 111 , 114 , 118 ].…”
Section: Cancer Mediation In Vitro and mentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, 22 presents potent proapoptotic and anti-angiogenic assets in vitro and in vivo , suggesting it to be a potential and promising remedy for treatment of ER-negative breast cancer. Other in vivo rodent studies not specifically reviewed here are likewise encouraging that the wide-ranging MAC family of anti-inflammatory and anti-cancer agents may well be able to address the corresponding debilitating conditions in humans sometime in the future [ 8 , 15 , 16 , 17 , 67 , 68 , 90 , 97 , 110 , 111 , 114 , 118 ].…”
Section: Cancer Mediation In Vitro and mentioning
confidence: 77%
“…Compound 188 , decorated with three methoxy groups at ortho and para terminal ring sites, is particularly attractive with an IC 50 within the 10 −6 M range corresponding to an inhibitory potency of more than 50-fold higher than curcumin. Suarez and colleagues prepared a similar subset of compounds 61 , 180 , 181 , 191 and 192 ( Figure 8 and Figure 16 ) and tested them against several tumor cell lines [ 97 ]. All the compounds exhibited different degrees of inhibitory activity against colon cancer cells HT-29, but analogs 61 , 180 and 181 furnished superior potency (IC 50 < 2.3 μM).…”
Section: Cancer Mediation In Vitro and mentioning
confidence: 99%
“…J. A. Quincoces Suarez et al [48] found that the set of synthetic compound 21 exhibited high antitumoral activeties regarding in vitro screening against several human tumor cell lines as lung carcinoma NCI-460, melanoma UACC-62, breast MCF-7, colon HT-29, renal 786-O, ovarian OVCAR-03 and ovarian expressing the compound, a strong electron-donating moiety may remove the bioactivity and a strong electron-withdrawing one may reduce it; 3) The acetone and cyclohexanone spacers are much more favorable than the cyclopentanone one; 4) The introduction of heteroaromatic ring is also pharmacologically accessible. And the following conclusions about SAR were drawn by the the research group of H. Yamakoshi; 5) Bis(aryl methylidene) acetone serves as the most promising skeleton for eliciting cytotoxicity; 6) The 3-oxo-1,4-pentadiene structure is essential for eliciting cytotoxicity; 7) Hexa-substituted compounds exhibit strong activities; 8) 3,4,5-Hexasubstitution results in the highest potency; 9) The symmetry between two aryl rings is important for tetra-substituted analogues but not a requirement for hexa-substituted analogues; 10) para-positions are allowed to introduce of additional functional groups for use as molecular probes.…”
Section: Structure Activity Relationship Analysis Of the Mono-carbonymentioning
confidence: 97%
“…A method for the preparation of an kind of mono-carbonyl analogues of curcumin, by Claisen condensation, starting from vanillin or vanillin derivatives, respectively, and acetone in acid medium under ultrasonic irradiation conditions with good yield and purity, which was patented in 2002, was adopted by J. A. Quincoces Suarez et al [48]. They also synthesized some mono-carbonyl analogues of curcumin under ultrasonic irradiation (40 kHz) in the presence of concentrated hydrochloric acid with good yield.…”
Section: Synthesis Of the Mono-carbonyl Analogues Of Curcuminmentioning
confidence: 99%
“…Substituents on the 4/4′‐position of curcumin may represent an important pharmacophore for biological activity [Ohtsu et al, 2002; Lin et al, 2006a, 2006b; Quincoces Suarez et al, 2010]. The curcumin analog ASC‐J9, which has a methoxy group at the 4/4′‐position had enhanced anti‐androgenic activity and cytotoxicity against prostate cancer cell lines [Lin et al, 2006a, 2006b; Shi et al, 2009].…”
Section: Introductionmentioning
confidence: 99%